1995
DOI: 10.1002/1097-0142(19951215)76:12<2449::aid-cncr2820761208>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic spectrum of resected extraductal mass-forming intrahepatic cholangiocarcinoma

Abstract: Background. The mode of tumor growth of intrahepatic cholangiocarcinoma (CC) varies considerably from patient to patient. This study describes the clinicopathologic variety of the extraductal mass‐forming type of CC. Methods. Patients with CC characterized by an extraductal mass (n = 26) who underwent hepatectomy from 1976 through 1992 were clinicopathologically classified into three types: Type I (n = 7), no biliary stricture; Type II (n = 13), biliary stricture without jaundice; and Type III (n = 6), biliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 14 publications
6
45
2
Order By: Relevance
“…Follow-up of patients with HCV infection therefore can detect many cases of ICC as well as HCC. Although serum concentrations of carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 are commonly measured to detect and monitor of ICC, insufficient sensitivity and specificity has been a problem with using these established markers in this form of cancer Mizumoto, 1984, 1990;Wang et al, 1994;Yamanaka et al, 1995;Nakamura et al, 1996;Chu et al, 1997;Kim et al, 1999). A more accurate marker for ICC is needed.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Follow-up of patients with HCV infection therefore can detect many cases of ICC as well as HCC. Although serum concentrations of carcinoembryonic antigen (CEA) and carbohydrate antigen (CA) 19-9 are commonly measured to detect and monitor of ICC, insufficient sensitivity and specificity has been a problem with using these established markers in this form of cancer Mizumoto, 1984, 1990;Wang et al, 1994;Yamanaka et al, 1995;Nakamura et al, 1996;Chu et al, 1997;Kim et al, 1999). A more accurate marker for ICC is needed.…”
supporting
confidence: 92%
“…Kubo et al (1995) reported that a high-serum CEA concentration strongly suggests ICC in patients with hepatolithiasis, even when no hepatic tumour is detected. Generally, however, serum CEA concentrations are elevated in only 20 -45% of patients with ICC (Yamanaka et al, 1995;Chu et al, 1997;Harrison et al, 1998;Kashihara et al, 1998;Kim et al, 1999;Uenishi et al, 2001). In the present study, serum CEA also showed a low sensitivity for ICC (34.8%).…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Iccmentioning
confidence: 99%
“…In patients with hepatolithiasis, fibrotic masses in the bile duct walls and periductal hepatic parenchyma are often seen as a form of periductal tumorlike lesions and may appear similar to cholangiocarcinoma on CT [19]. Furthermore, in patients with hepatolithiasis, the stricture or stenosis caused by cholangiocarcinoma may not be easy to differentiate from that caused by stones [6,10,20].…”
contrasting
confidence: 68%
“…Because surgery remains the only intervention offering the possibility of a cure [25], early detection of cholangiocarcinoma is essential in hepatolithiasis patients; early detection raises the chance that a patient can be included as a surgical candidate and may consequently improve their prognosis. However, the diagnosis may be easily delayed because the symptoms related to cholangiocarcinoma are vague and are also similar to those of hepatolithiasis [10,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation